Stubby-Root Nematode, Trichodorus obtusus Cobb (Nematoda: Adenophorea: Triplonchida: Diphtherophorina: Trichodoridea: Trichodoridae) - William T. Crow (EDIS, 2005)
Nematodes in the family Trichodoridae (Thorne, 1935) Siddiqi, 1961, are commonly called "stubby-root" nematodes, because feeding by these nematodes can cause a stunted or "stubby" appearing root system. Trichodorus obtusus is one of the most damaging nematodes on turfgrasses, but also may cause damage to other crops. This document is EENY-340, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2004.